Strategi Guru Pendidikan Agama Kristen dalam Meningkatkan Minat Belajar Peserta Didik - Logius Logius; Gianto Gianto; Saenom Saenom; Marthen Mau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
Christian religious education teachers need to have strategies to increase the learning interest of students in grades three to six in elementary education institutions including at State Elementary School 21 Agak Hulu. Christian religious education teachers who carry out their main duties at State Elementary School 21 Agak Hulu because some students at the school do not have the interest in learning or the desire to learn is very lacking, so that the learning outcomes they receive are very unsatisfactory. This article aims to discuss the strategies of Christian religious education teachers in increasing student learning interest, so that students increasingly increase their interest in participating in learning, both at school and at home responsibly. The methodology used in this study is qualitative with a data processing approach, namely observation, interviews and documentation. The formulation of the theoretical results of this thesis is that if Christian religious education teachers have loyalty in encouraging students to increase their interest in learning to the maximum, then students will be more motivated in the learning process at home and at school. Thus, the simple conclusion of this thesis is that the more Christian religious education teachers have strategies to motivate students in the learning process at school, the more students will maximize and optimize their learning interest, especially students at Agak Hulu 21 Public Elementary School.